Informator . no. 52, 1981 - Biuro Informacyjne Regionu Środkowo-Wschodniego NSZZ "Solidarność", [ed. M. Sobieraj et al.] (NSZZ "Solidarność" Region Środkowo-Wschodni, 1981)
Creation and circulation: For trade-union use; After introduction of the Martial Law publication suspended. Republished underground in January 1982